Orthograde dihydropyridine receptor signal regulates ryanodine receptor passive leak - Eltit, José Miguel (National Academy of Sciences, 2011)
The skeletal muscle dihydropyridine receptor (DHPR) and ryanodine receptor (RyR1) are known to engage a form of conformation coupling essential for muscle contraction in response to depolarization, referred to as excitation–contraction coupling. Here we use WT and Ca(V)1.1 null (dysgenic) myotubes to provide evidence for an unexplored RyR1–DHPR interaction that regulates the transition of the RyR1 between gating and leak states. Using double-barreled Ca(2+)-selective microelectrodes, we demonstrate that the lack of Ca(V)1.1 expression was associated with an increased myoplasmic resting [Ca(2+)] ([Ca(2+)](rest)), increased resting sarcolemmal Ca(2+) entry, and decreased sarcoplasmic reticulum (SR) Ca(2+) loading. Pharmacological control of the RyR1 leak state, using bastadin 5, reverted the three parameters to WT levels. The fact that Ca(2+) sparks are not more frequent in dysgenic than in WT myotubes adds support to the hypothesis that the leak state is a conformation distinct from gating RyR1s. We conclude from these data that this orthograde DHPR-to-RyR1 signal inhibits the transition of gated RyR1s into the leak state. Further, it suggests that the DHPR-uncoupled RyR1 population in WT muscle has a higher propensity to be in the leak conformation. RyR1 leak functions are to keep [Ca(2+)](rest) and the SR Ca(2+) content in the physiological range and thus maintain normal intracellular Ca(2+) homeostasis.